Addition of plerixafor to G-CSF in poor mobilizing healthy related donors overcame mobilization failure: An observational case series on behalf of the Grupo Español de Trasplante Hematopoyético (GETH). (April 2021) - Cid, Joan; Monsalvo, Silvia; Castillo, Carlos; Pascual, Cristina; Moreno-Jiménez, Gemma; López-Parra, Miriam; Andón, Concepción; Guerra, Luisa; Esquirol, Albert; Sánchez-Ortega, Isabel; Ortega, Sandra; Zalba, Saioa; et al.
Abstract: Plerixafor (Mozobil, Sanofi) is approved for using in patients with lymphoma and multiple myeloma when steady-state mobilization strategies fail. Although off-label use of plerixafor in healthy related donors (HRD) is known, limited data are available and no recommendations exist to guide its use in this setting. With the aim of collecting data from HRDs who received plerixafor in our country, we designed an observational case series study within the Spanish Group of Hematopoietic Transplant and Cell Therapy (GETH). Plerixafor was administered subcutaneously to 30 HRDs at a median dose of 0.24 mg/Kg (interquartile range (IQR): 0.23−0.25) because mobilization failure after using mobilization with G-CSF (mobilization failure was defined as collection of <4.0 × 10 6 CD34+ cells/Kg recipient). All HRDs received G-CSF at a median dose of 11 μg/Kg/day (IQR: 10–12) for 4–5 days. Leukocytapheresis after G-CSF mobilization was performed in 23 (77 %) HRDs collecting a median of 1.6 × 10 6 CD34+ cells/Kg recipient weight (IQR: 0.9–2.5). Addition of plerixafor allowed the collection of a higher median number of CD34 cells (4.98 × 10 6 CD34+ cells/Kg recipient weight (IQR: 3.5–5.8)) when compared with the collection of CD34+ cells with G-CSF alone (p < 0.01). The final median total number of CD34+ cells collected was 6.1 × 10 6 /Kg recipient weight (IQR: 4.8–7.3). Mild adverse events related with plerixafor administration were reported in 8 (27 %) donors. In conclusion, addition of plerixafor after G-CSF mobilization failure in HRDs allowed collecting higher number of CD34+ cells in comparison with steady-state mobilization.